Miliary tuberculosis with meningovascular involvement - Mesía-Ángeles, Diego (2023)
The case of a 20-year-old male patient is presented, with an illness of one week characterized by asthenia, hyporexia, nausea, vomiting, neck stiffness, intermittent headache of intensity 9/10, fever quantified at 38.5. °C, scant dry cough, weight loss and left hemiparesis without loss of consciousness. Serological tests, including HIV, were negative. The spinal fluid showed pleocytosis with a predominance of mononuclear cells, hyperproteinorrachia and hypoglycorrhachia, with a positive GeneXpert MTB/RIF test for M. tuberculosis resistant to rifampicin, in addition to a positive sputum smear for the same germ. The images showed a miliary pattern and vascular compromise (bilateral hypodensities at the level of the basal ganglia and internal capsule). He was treated as multidrug-resistant systemic tuberculosis with a favorable outcome.